SINTESIS 4,10,16,22-TETRAMETOKSIKALIKS[4]ARENA DARI MINYAK ADAS (Synthesis of 4,10,16,22-Tetramethoxycalix[4]Arene from Anise Oil) - Sardjono, Ratnaningsih Eko (Jurnal Pengajaran MIPA, 2001)
One kind of calixarenes, i.e. 4,10,16,22-tetramethoxycalix[4]arene (4), has been synthesized from anethole (1), which was isolated from anise oil. The synthesis of 4 was carried out via acid-catalyzed procedure. The reaction route consists of three stages, i.e. (i) oxidation of 1 with KMnO4 at 40oC for 15 minutes, (ii) reduction p-anisaldehyde (2) with NaBH4 at 76oC for 3 hours, andÂ  (iii) cyclotetramerization of p-anisilalcohol (3) with AlCl3 at 20oC for 2 hours. Oxidation of 1 produced 2 in 77%, whereas reduction of 2 gave 3 in 55 %. The cyclotetramerization of 3 yielded 4 in 95 %.